2019
DOI: 10.1093/jas/skz192
|View full text |Cite
|
Sign up to set email alerts
|

Identification of resilient sows in porcine reproductive and respiratory syndrome virus–infected farms1

Abstract: The identification of resilient sows can improve reproductive performance in farms exposed to multiple challenges. A common challenge is the porcine reproductive and respiratory syndrome virus (PRRSV). A key issue to deal with disease resilience is to set up a feasible phenotyping strategy. Our aim was to develop a phenotyping criterion to discriminate susceptible from resilient sows in PRRSV-infected farms. A total of 517 Landrace x Large White gilts were classified as resilient (R) or susceptible (S) to PRRS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 31 publications
(26 reference statements)
3
25
0
Order By: Relevance
“…Serão et al (2016), using the same PRRS ELISA test as in our study, reported h 2 estimates ranging from 0.28 ± 0.04 to 0.47 ± 0.06, as the proportion of seroconverted animals increased in the dataset; however, there was no confirmation on whether the replacement gilts in were PRRSV-vaccinated or PRRSV-infected or even both. More similar to our study, Abella et al (2019) estimated h 2 for S/P ratio at 42 days after PRRSV vaccination and obtained a higher h 2 estimate than we observed in our study (0.69 ± 0.10). Although they used the same ELISA test as us, the animals in their study were growing pigs at 6-7 weeks of age, and it is possible that the redirect of energy being used to growth for antibody production may have affected future performance.…”
Section: Heritabilitiessupporting
confidence: 90%
See 3 more Smart Citations
“…Serão et al (2016), using the same PRRS ELISA test as in our study, reported h 2 estimates ranging from 0.28 ± 0.04 to 0.47 ± 0.06, as the proportion of seroconverted animals increased in the dataset; however, there was no confirmation on whether the replacement gilts in were PRRSV-vaccinated or PRRSV-infected or even both. More similar to our study, Abella et al (2019) estimated h 2 for S/P ratio at 42 days after PRRSV vaccination and obtained a higher h 2 estimate than we observed in our study (0.69 ± 0.10). Although they used the same ELISA test as us, the animals in their study were growing pigs at 6-7 weeks of age, and it is possible that the redirect of energy being used to growth for antibody production may have affected future performance.…”
Section: Heritabilitiessupporting
confidence: 90%
“…Although they used the same ELISA test as us, the animals in their study were growing pigs at 6-7 weeks of age, and it is possible that the redirect of energy being used to growth for antibody production may have affected future performance. Another important point to be highlighted is that in the study by Abella et al (2019), the herds were endemic for PRRS, and, therefore, the animals were in constant health challenge during vaccination and farrowing. Therefore, our study is the first one, to the best of our knowledge, to estimate h 2 for S/P ratio in PRRS-vaccinated F1 replacement gilts.…”
Section: Heritabilitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Infectious diseases are well known to cause productivity losses in the swine industry (Lee et al, 2012;Lewis et al, 2007), motivating the investigation of traits related to disease resilience for genetic selection. It has been shown that there is genetic variation in total antibody (Ab) response to swine pathogens, such as porcine reproductive and respiratory syndrome (PRRS) virus (PRRSV) (Serão et al, 2014;Hess et al, 2018;Abella et al, 2019). Selection of more resilient animals could decrease the losses caused by the decreased performance of animals exposed to pathogens.…”
Section: Introductionmentioning
confidence: 99%